A three-dimensional high-resolution reservoir model of the Eocene Shahejie Formation in Bohai Bay Basin, integrating stratigraphic forward modeling and geostatistics. (April 2017) - Yin, Xiangdong; Lu, Shuangfang; Wang, Pengfei; Wang, Qiming; Wang, Wei; Yao, Tongyun
Abstract: Reservoir characterization based on geostatistics method requires well constraints (e.g. seismic data with high quality) to predict inter-well reservoir quality that is conformed to geological laws. Nevertheless, the resolution of seismic data in multiple basins or reservoirs is not high enough to recognize the distribution of different types of sand bodies. In this paper, we propose a new method to improve the precision of reservoir characterization: reservoir modeling with the constrains of sedimentary process model and sedimentary microfacies. We employed stratigraphic forward modeling, a process-based method, to constrain the reservoir modeling in one oil-bearing interval of the third member of Eocene Shahejie Formation in J-Oilfield of Liaoxi Sag, Bohai Bay Basin. We divide reservoir modeling into two orders using different types of constrains. In the first order, we use the simulated shale model from stratigraphic forward model that is corrected by wells data as a 3D trend volume to constrain the reservoir sand-shale modeling. In the second order, different types of sedimentary microfacies in the sandy part of the model are further recognized and simulated within the constrains of sedimentary microfacies maps. Consequently, the porosity, permeability and oil saturation are modeled under the control of precise sedimentary microfacies model. The high-resolution reservoir model shows that the porosity, permeability and oil saturation of distributary channel is generally above 20%, 10md and 50%, respectively, which are much higher than that of other types of sedimentary microfacies. It can be concluded that comparing to other types of sedimentary facies, distributary channel has better physical properties and more oil accumulation in the fan-delta front and therefore is the most favorable zones for petroleum development in the research area. Highlights: The combination of stratigraphic forward model and geostatistics is a perfect way. Stratigraphic forward modeling is a good method to predict lithology distribution. Sand-shale model is set up under the constrain of stratigraphic forward model. Sedimentary microfacies is recognized within the constrains of facies trend body. Distributary channel has better physical properties and more oil accumulation.